Self-medication consultations in community pharmacy - Veiga, Paulo (2021)
Background: Community pharmacy teams (CPTs) have an established role in assisting self-medication, contributing to the safe and effective use of non-prescription medicines. Objective: The study aimed to describe CPTs’ performance in self-medication consultation, client-reported outcomes, and satisfaction. A secondary purpose was to develop an explanatory model for better understanding clients’ satisfaction with this service. Methods: Descriptive, cross-sectional exploratory study. Data were collected in a purposive sample of pharmacy clients recruited in six community pharmacies in Portugal. CPTs adopted a structured approach to self-medication consultations, encompassing 11 quality criteria (five for case evaluation and six for counselling). An evaluation score, a counselling score and an overall quality score were estimated. Client-reported outcomes and satisfaction were ascertained via a follow-up telephone interview. Besides descriptive statistics, the association with several independent variables on the clients’ overall satisfaction was explored, using linear regression. Results: Product-based dispensing was more frequent for lower educated clients. Reported compliance with the criteria by CPTs was overall high (93.95% of maximum compliance), mostly missing the ‘other medication’ questioning. Most clients (93%) reported improvement after the consultation. Clients’ satisfaction score was 4.70 out of 5. The variables that seem to better explain clients’ overall satisfaction are pharmacy loyalty, the evaluation score, and the female gender. Conclusions: Clients’ reported outcomes were favourable, as well as satisfaction with the service. Clients’ satisfaction appears to be determined by consultation quality (evaluation score), suggesting the advancement of the pharmacists’ clinical role. A larger study is warranted to confirm these findings.